Financial Crisis in Greece: Challenges and Threats for the Global Economy - Dudin, Mihail Nikolaevich; Gayduk, Vladimir Ivanovich; Sekerin, Vladimir Dmitrievich; Bank, Sergey Valeryevich; Gorohova, Anna Evgenevna (International Journal of Economics and Financial Issues, 2016)
This article is devoted to the research of the reasons behind the occurrence of the crisis in Greece and challenges and opportunities that arise both for the global economy and the economy of the European Union (EU). The theme of the article is rather urgent by reason of incomplete understanding of the nature of the crisis in Greece, its suddenness and impossibility to predict its consequences for the global economic relations. The main goal of stating the materials in this article is to analyze the reasons of the crisis in Greece in terms of economy, history, sociology, and other scientific areas. Basic tasks include the following: To reveal a complex of all aspects of the economic crisis in Greece, to analyze its deep (historical) reasons, and to reveal challenges for the world economy and economy of the EU and Russia related to the Greek crisis. The flowing basic conclusions were made within the article: (1) The crisis in Greece has not only economic but also political reasons. However, at the same time the Greek crisis cannot be solved only in terms of economy. It is necessary to take systematic measures to solve the occurred problems, (2) the economic crisis is only a visible part of structural problems of the Greek economy. At the present time a great number of social, technological, and humanitarian problems have been hidden behind the mass revealing of economic crisis tendencies, (3) the basic reason of the economic crisis is in the incompliance of social and economic model of the Greece development with the EU based on the West-European logics of functioning. Practical application of the results of this work by scientists and economists will allow to objectively reconsider the essence of the Greek crisis, and make conclusions that will contribute to the development of recommendations aiming at preventing the crisis in other countries. Keywords: Greece, Economic Crisis, European Union, Global Economy JEL Classifications: G01, N24, F63